The Relationship between Patient Satisfaction Level and Teledentistry Utilization at Azka Nadhifa Dental Polyclinic Makassar - Wijaya, Muhammad Fajrin; Abdi, Muhammad Jayadi; Andira, Erni (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2023)
Introduction: The development of communication technology has created new innovations in the field of dentistry by combining telecommunications and dentistry technology which is called teledentistry. Teledentistry is a service alternative that combines telecommunications and dentistry technology to exchange clinical information and images remotely for treatment planning and dental consultations. Objective: To analyze the relationship between patient satisfaction level and the utilization of teledentistry at the Azka Nadhifa dental polyclinic, Makassar. Methods: This study used an analytic research design with a cross-sectional research design. The statistical test used is the Spearman correlation test. The sample in this study consisted of 96 samples. Results: Based on the results of the Spearman rank correlation test, it shows a p-value of 0.002 which is smaller than 0.05 (p-value <0.05). This shows that there is a relationship between the level of satisfaction with the use of teledentistry. Conclusion: Based on the results of this study it shows that there is a relationship between the level of patient satisfaction and the use of teledentistry at the Azka Nadhifa dental polyclinic, Makassar